Optical Fiber‐Based Gas Sensing for Early Warning of Thermal Runaway in Lithium‐Ion Batteries - Xuanren Chen; Lin Gan; Xin Guo (Advanced Sensor Research, 2023)
Abstract Owing to constantly increasing energy density and power density, thermal runaway is becoming the most dangerous event in lithium‐ion batteries, while gas sensing can provide the earliest and clearest signals for forewarning the advent of thermal runaway. However, gas‐sensing signals are not included in current battery management systems (BMSs). Especially for the challenging in‐cell sensing, gas sensing demonstrates significant advantages over out‐of‐cell sensing in the aspect of collecting signals precisely and in a timely manner. The integration of gas sensing with batteries is an important and valuable topic. In this review, the necessity and challenge of in‐cell sensing are expounded, the importance and promise of in‐cell gas sensing are highlighted, optical fiber‐based gas sensing technologies for in‐cell applications are summarized, and the engineering issues of integrating sensors with battery system are discussed. The topic of this article deserves more attention and efforts for the development of cell‐level BMSs and safe batteries in future.